Evaluasi Penyelenggara Pelayanan Publik di Puskesmas Sidodadi melalui PEKPPP - Holidya, Holidya; Manggalau , Singgih (Innovative: Journal Of Social Science Research, 2025)
The Public Service Performance Evaluation was created by the Minister of State Apparatus Empowerment (Menpan) which was implemented in 2022 Number 29 concerning Monitoring and Evaluation of the Performance of the Implementation of Public Services with online-based monitoring (PEKPPP). With this online-based monitoring, it will later make it easier to systematically measure a work unit in a certain time to obtain materials for the preparation of recommendations in service improvement. This study aims to evaluate the implementation of public services at the Sidodadi Health Center in Sidoarjo Regency. Starting from 2022 to 2024, in order to identify the level of service quality, obstacles faced, and necessary improvement steps. The evaluation was carried out using a qualitative-descriptive approach, namely observation techniques and document analysis. This research focuses on key aspects of services, including accessibility, efficiency, responsiveness, and community satisfaction. The results of the study show that the Sidodadi Health Center has not fully achieved several success indicators because there are several obstacles that need to be overcome, such as limited human resources, inadequate facilities, and slow administrative processes. Based on these findings, strategic measures such as increasing the capacity of health workers, modernizing facilities, and implementing a service digitalization system are recommended to improve service quality. This research is expected to be a reference for local governments and related parties in efforts to improve the quality of public services in the health sector, especially at the Puskesmas level.